CRM197-conjugated serogroup C meningococcal capsular polysaccharide, but not the native polysaccharide, induces persistent antigen-specific memory B cells. - Kelly, D; Snape, MD; Clutterbuck, E; Cutterbuck, E; Green, S; Snowden, C; Diggle, L; Yu, L; Borkowski, A; Moxon, E; Pollard, A (2006)
Neisseria meningitidis is one of the leading causes of bacterial meningitis and septicemia in children. Vaccines containing the purified polysaccharide capsule from the organism, a T cell-independent antigen, have been available for decades but do not appear to provide protection in infancy or immunologic memory as measured by antibody responses. By contrast, T cell-dependent serogroup C protein-polysaccharide conjugate vaccines protect against serogroup C meningococcal disease from infancy onward and prime for immunologic memory. We compared the magnitude and kinetics of plasma cell and memory B-cell responses to a meningococcal plain polysaccharide vaccine and a serogroup C glycoconjugate vaccine in adolescents previously primed with the conjugate vaccine. Plasma cell kinetics were similar for both vaccines, though the magnitude of the response was greater for the glycoconjugate. In contrast to the glycoconjugate vaccine, the plain polysaccharide vaccine did not induce a persistent immunoglobulin G (IgG) memory B-cell response. This is the first study to directly show that serogroup C meningococcal glycoconjugate vaccines induce persistent production of memory B cells and that plain polysaccharide vaccines do not, supporting the use of the conjugate vaccine for sustained population protection. Detection of peripheral blood memory B-cell responses after vaccination may be a useful signature of successful induction of immunologic memory during novel vaccine evaluation.